2008
DOI: 10.1111/j.1365-2044.2008.05681.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in rapid sequence induction techniques: current practice in Wales

Abstract: SummaryA questionnaire survey examining rapid sequence induction techniques was sent to all anaesthetists in Wales. The questionnaire presented five common clinical scenarios: emergency appendicectomy; elective knee arthroscopy with a symptomatic hiatus hernia; elective knee arthroscopy with an asymptomatic hiatus hernia; elective Caesarean section; and emergency laparotomy for bowel obstruction. Completed surveys were received from 421 anaesthetists, a 68% response rate. Rapid sequence induction was chosen by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 32 publications
3
54
2
4
Order By: Relevance
“…Although priming [17] and timing principles [18] using rapid-onset rocuronium have been reported to be effective for rapid sequence intubation, suxamethonium seems to be clinically preferred rather than rocuronium as a neuromuscular blocking agent for patients with specific risks of pulmonary aspiration. In fact, a survey of variation of rapid sequence induction techniques in Wales reported that suxamethonium was currently used for 97% of cesarean sections, 94% of bowel obstructions, and 85% of appendectomies; in contrast, rocuronium was used only in 2-12% of patients [2]. A retrospective case-review analysis of 250 patients undergoing appendectomy in a 1-year period also revealed that suxamethonium use was 80%, with 96% of these patients receiving rocuronium precurarization [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although priming [17] and timing principles [18] using rapid-onset rocuronium have been reported to be effective for rapid sequence intubation, suxamethonium seems to be clinically preferred rather than rocuronium as a neuromuscular blocking agent for patients with specific risks of pulmonary aspiration. In fact, a survey of variation of rapid sequence induction techniques in Wales reported that suxamethonium was currently used for 97% of cesarean sections, 94% of bowel obstructions, and 85% of appendectomies; in contrast, rocuronium was used only in 2-12% of patients [2]. A retrospective case-review analysis of 250 patients undergoing appendectomy in a 1-year period also revealed that suxamethonium use was 80%, with 96% of these patients receiving rocuronium precurarization [3].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rapid sequence intubation is frequently used to decrease the risk of pulmonary aspiration of gastric contents in a patient with a full stomach. Suxamethonium enables us to considerably shorten the interval from the patient's loss of consciousness following hypnotics to tracheal intubation and is considered to be appropriate for rapid sequence intubation [2,3]. For such occasions, precurarization with a small dose of a nondepolarizing neuromuscular blocking agent has been widely used to prevent muscle fasciculation induced by suxamethonium and rise in intraabdominal pressure [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Deliver appropriate doses of induction agent/ neuromuscular blocking drug: Thiopental remains the most commonly used drug in UK for induction during rapid sequence induction in obstetrics [89][90][91]. However, the case for its continued use has greatly diminished; there are strong recommendations to use propofol instead for reasons that include familiarity, supply, ease of drawing up and fewer drug errors [90,92,93].…”
Section: Rapid Sequence Inductionmentioning
confidence: 99%
“…Encouraging more effective use of inhalational agents and better management of airway difficulties (including consideration of further induction agent) and of regional anaesthesia (especially failed) is really nothing new, and should not change the thrust of what we are already doing. Other potential changes still linger in the background: opioids are more likely to be omitted from rapid sequence induction for obstetrics than in other settings [13,29], because of concerns about the fetus and the ability to wake a woman in the event of failed intubation, but these concerns have no evidence base. The choice of neuromuscular blocking drug to enable intubation, potentially switching from suxamethonium to rocuronium, is also a question yet to be decided.…”
Section: Maternal Mortality: Moody Skiesmentioning
confidence: 99%